Bioenergy production by integrated microwave-assisted torrefaction and pyrolysis - Mohamad Aziz N.A.; Mohamed H.; Kania D.; Ong H.C.; Zainal B.S.; Junoh H.; Ker P.J.; Silitonga A.S. (Elsevier Ltd, 2025)
The global shift towards renewable and sustainable energy sources demands a more efficient conversion of agricultural biomass into sustainable energy. The integration of microwave heating with thermochemical conversion processes of biomass into biofuels has garnered attention due to faster reaction times, improved selectivity, and reduced energy consumption compared to conventional heating. Despite the promise shown by various thermochemical approaches, there remains a gap in the literature regarding systematic reviews of microwave-assisted torrefaction and pyrolysis as an integrated technology and comparisons to other thermochemical routes to assess its potential. Therefore, this review addresses recent advancements in microwave-assisted torrefaction and pyrolysis, discussing feasibility, optimization studies, key factors influencing product yield and properties (bio-oil, biogas, and biochar), and future research directions. The assessment reveals the merits and drawbacks of this combined technology compared to other integrated approaches like gasification, combustion, and liquefaction. The outcomes have shown solid yields exceeding 95 % as the main product and 37 % of bio-oil yield. However, previous research underestimates the complexities of establishing microwave reactors, particularly in scaling up. The findings emphasize the potential of microwave-assisted torrefaction and pyrolysis as an integrated process with broad implications for sustainable energy transitions. ? 2023 Elsevier Ltd